Association between family satisfaction and caregiver burden in cancer patients receiving outreach palliative care at home. Issue 3 (2nd May 2017) - Naoki, Yoko; Matsuda, Yoshinobu; Maeda, Isseki; Kamino, Hideka; Kozaki, Yoko; Tokoro, Akihiro; Maki, Norimasa; Takada, Minoru
ABSTRACT: Objective: Little is known about the associations between family satisfaction with end-of-life care and caregiver burden. We conducted a researcher-assisted questionnaire survey to clarify the impact of caregiver burden on family satisfaction and to determine the types of burden that decrease family satisfaction. Method: Bereaved family caregivers of patients with advanced cancer who received our outreach palliative care service were retrospectively identified. Family satisfaction with the end-of-life care provided by the palliative care service and caregiver burden were quantified using the Japanese versions of the FAMCARE Scale and the Zarit Burden Interview (ZBI), respectively. Results: Our study subjects included 23 family caregivers. The mean scores on the FAMCARE Scale and the ZBI for the total population were 72.8 ± 11.2 and 22.8 ± 17.3, respectively, indicating moderate-to-high satisfaction and low-to-moderate burden. Caregiver burden had a strong negative correlation to family satisfaction with end-of-life care (Spearman's rho [ρ] = −0.560, p = 0.005), which remained after adjustment for potential confounders (standardized beta [β] = −0.563, p = 0.01). Several burden items—including loss of control, personal time, social engagement with others, feeling angry with the patient, feeling that the patient wants more help than he/she needs, and a wish to leave the care to someone else—were associated with decreased satisfaction. The major cause of dissatisfaction for family members included the information provided regarding prognosis, family conferences with medical professionals, and the method of involvement of family members in care decisions. Significance of results: Caregiver burden can be a barrier to family satisfaction with end-of-life care at home. A home care model focused on caregiver burden could improve end-of-life experiences for patients and family caregivers.